Migrants leaving mega-cities: Where they move and why prices matter - Eva-Maria Egger (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Traditional economic models predict rural to urban migration during the structural transformation of an economy. In middle-income countries, it is less clear which direction of migration to expect. In this paper I show that in Brazil as many people move out of as into metropolitan cities, and they mostly move to mid-sized towns. I estimate the determinants of out-migrants' destination choice, accounting for differences in earnings, living costs, and amenities, and I test whether the migrants gain economically by accepting lower wages but enjoying lower living costs. The findings suggest that the destination choice of out-migrants minimizes the costs of moving. On average, city-leavers realize higher real wages, including lowskilled migrants who would lose out in nominal terms. The paper thus provides evidence on economic incentives to leave big cities in a middle-income country.
Keywords: J61; R23; C35; 330; Brazil; internal migration; prices; secondary towns